2014
DOI: 10.1371/journal.pntd.0002917
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulating Effects of NKT Cells in a Physiologically Low Dose Leishmania major Infection Model after αGalCer Analog PBS57 Stimulation

Abstract: Leishmaniasis is a parasitic infection affecting ∼12 million people worldwide, mostly in developing countries. Treatment options are limited and no effective vaccines exist to date. Natural Killer T (NKT) cells are a conserved innate-like lymphocyte population with immunomodulating effects in various settings. A number of reports state a role of NKT cells in different models of Leishmania infection. Here, we investigated the effect of NKT cells in a physiologically relevant, intradermal low dose infection mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
(28 reference statements)
3
7
1
2
Order By: Relevance
“…Studies on the distribution and function of NKT cells in CL are scarce and mostly focused on the role of NKT cells as producer of cytokines, leading to an inflammatory response type I or II through their interaction with dendritic cells . In our study, there were no differences in NKT cells frequency among the groups of patients and HI.…”
Section: Discussioncontrasting
confidence: 49%
“…Studies on the distribution and function of NKT cells in CL are scarce and mostly focused on the role of NKT cells as producer of cytokines, leading to an inflammatory response type I or II through their interaction with dendritic cells . In our study, there were no differences in NKT cells frequency among the groups of patients and HI.…”
Section: Discussioncontrasting
confidence: 49%
“…Our ex vivo analyses of whole blood cells, patients with ACL demonstrated an increase in CD69 expression in iNKT cells compared to all study groups, which was independent of TLA stimulation. Interestingly, studies in murine models also demonstrated that this highly activated state in this small subpopulation could be important for the overall immune response against Leishmania . Human studies demonstrated that CD3+ CD161+ cells from patients infected by L. donovani presented a higher activation in bone marrow cells than in the PBMC and that CD3+ CD161+ PBMC cells did not show activation differences when comparing VL cases and healthy endemic groups .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers, using a wild‐type CD57BL/6 (WT) and iNKT‐deficient (Jα18‐/‐) murine lineages, showed that, while WT mice controlled the infection, the iNKT‐deficient mice presented higher parasite loads in all time points studied. However, the role of iNKT in human VL and CL remains poorly understood, mainly due to controversial data in murine models.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we suspect that NK cells are also not the important granzyme-secreting cells, at least not in B6 mice, since B6 bg/bg Ϫ/Ϫ (beige) mice, deficient in NK cell cytolytic activity, show no early defect in controlling L. donovani in the liver (24,68,69); NK cells are also not cytolytic in B6 WT mice infected with visceral Leishmania infantum (70). Currently, it is also unclear what antileishmanial defense role NKT cells play in B6 mice, in view of the contrasting results in the L. donovani model (71,72) and the demonstration that NKT cells promote cutaneous Leishmania major infection (73). Further analysis, then, in both B6 and 129/Sv mice will be needed to identify the relevant granzyme-secreting cells in L. donovani infection.…”
Section: Discussionmentioning
confidence: 99%